Design as a space of compromise between the global and the local - Zheleznyak, Olga (project baikal, 2021)
The contradictory integrity of the global and the local is viewed as a source of transnational and regional development. Design is an important aspect of glocalization, which ensures the “formulation” and introduction of basic ideas into the real life, and a space of compromise and interaction between the global and the local. It is clearly demonstrated by contemporary branding systems. Design as a scientific and educational space is presented in glocal discourses through the work of the Design Department of INRTU.